Modified method of lignocellulose content determination and its use for the analysis of selected herbs - precursors of biochars and activated carbons. (15th May 2023) - Gęca, Marlena; Wiśniewska, Małgorzata; Nowicki, Piotr
Highlights: Modified method of lignocellulose content determination was elaborated. Difficult lignin quantification with calibration curve usage was eliminated. New cellulose determination method was proposed. The developed procedure was checked on selected herbs. Abstract: Determination of extractives, lignin, hemicellulose, cellulose and mineral substance is a complex procedure. Lignin and hemicellulose are both alkali soluble and their mutual determination is disturbed. Moreover, the lignin occurs in two fractions - soluble and insoluble in acids, which make its determination difficult. In this paper a new, modified method of all the above components determination was described. The inaccuracies in methods reported in the literature so far were solved. There was applied not sophisticated equipment aimed at the costs reduction. The complicated, multistep lignin content determination was replaced by easier procedure of cellulose evaluation. Moreover the hemicellulose determination was improved (the error related with lignin dissolution in alkaline solution was eliminated). The presented method was used for the nettle, sage, lemon balm and mint herbs analyses. The herbs contain a small percentage of mineral substance and are very suitable for the activated carbons preparation. It has been shown that the content of hemicellulose affects the activated carbons surface area development, whereas the lignin content has influence on the concentration of total surface functional groups. Activated carbons with the best surface properties were obtained from the herbs containing high concentrations of hemicellulose and lignin.